How do you differentiate #f(x)=(1-lnx)/(1+lnx)# using the quotient rule?
# d/dx (1-lnx)/(1+lnx) = - ( 2 ) / ( x(1+lnx)^2 )#
Using the quotient rule, we have:
By signing up, you agree to our Terms of Service and Privacy Policy
To differentiate ( f(x) = \frac{1 - \ln(x)}{1 + \ln(x)} ) using the quotient rule:
- Identify ( u(x) = 1 - \ln(x) ) and ( v(x) = 1 + \ln(x) ).
- Apply the quotient rule formula: [ f'(x) = \frac{v(x)u'(x) - u(x)v'(x)}{[v(x)]^2} ].
- Compute the derivatives: [ u'(x) = \frac{d}{dx}(1 - \ln(x)) = -\frac{1}{x} ] [ v'(x) = \frac{d}{dx}(1 + \ln(x)) = \frac{1}{x} ]
- Substitute the derivatives and functions into the quotient rule formula: [ f'(x) = \frac{(1 + \ln(x))(-\frac{1}{x}) - (1 - \ln(x))(\frac{1}{x})}{(1 + \ln(x))^2} ].
- Simplify the expression: [ f'(x) = \frac{-1 - \ln(x) + \ln(x) - \ln^2(x)}{(1 + \ln(x))^2} ] [ f'(x) = \frac{-1 - \ln^2(x)}{(1 + \ln(x))^2} ].
So, the derivative of ( f(x) ) with respect to ( x ) is: [ f'(x) = \frac{-1 - \ln^2(x)}{(1 + \ln(x))^2} ].
By signing up, you agree to our Terms of Service and Privacy Policy
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
- How do you find the derivative of #2/(x+1)#?
- How do you use the chain rule to differentiate #y=8(x^4-x+1)^(3/4)#?
- What is the slope of the tangent line of #(x-y)^3e^y= C #, where C is an arbitrary constant, at #(-2,1)#?
- What is the derivative of #-4/x^2#?
- What is the implicit derivative of #3=(1-y)/x^2+xy #?
- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7